52 I'm on the Floor and Can't Get up and it's Really Annoying: A Qualitative Investigation of Patient and Staff Perceptions of Options for Getting up From the Floor Following A Fall. (16th March 2021) - Swancutt, D; Hope, S V; Kent, B; Robinson, M; Goodwin, V
Abstract: Background: Falls are the most common reason for ambulance call-outs resulting in non-conveyance. Even in the absence of injury, only half of those who have fallen can get themselves up off the floor. Many remain there for over an hour, increasing complications risks. It is feasible to teach people techniques to help get themselves off the floor, yet these techniques are rarely taught. To date, there are no published data on attitudes towards teaching and learning these techniques. Our study aimed to investigate patient, carer and staff attitudes towards seeking help and using techniques to get-up following a fall. Methods: A qualitative focus group and semi-structured interviews were conducted with 28 participants, including community-dwelling older people who had experienced a non-injurious fall, carers, physiotherapists, occupational therapists, paramedics and community first responders. Data were transcribed and analysed systematically using the Framework approach. A stakeholder group of falls experts and patients advised during analysis. Results: The data highlighted three areas contributing to an individual's capability to get-up following a fall: the environment (physical and social); physical ability; and degree of self-efficacy (attitude and beliefs about their own ability). These factors influenced each person's capability to manage their fall response. Staff described how they balance their responsibilities, prioritising the individual's immediate needs; this leaves limited time to address capability in the aforementioned three areas. Paramedics, routinely responding to falls, only receive training on getting-up techniques from within their peer-group. Therapists are aware of the skillset to breakdown the getting-up process, but, with limited time, select who to teach these techniques to. Conclusion: Neither therapists nor ambulance service staff routinely teach all those at risk of falling strategies on how to get-up. Interventions to positively impact on capability to get-up following a fall should include strategies that address the environment, physical ability and self-efficacy.